Serology based comprehensive study of Neospora infection in domestic animals in Hamedan province, Iran - Gharekhani, Jamal; Heidari, Heidar (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to determine seroprevalence of Neospora infection in cattle, sheep, horses, donkeys, and dogs in Hamedan province, Iran. Blood samples (n=2254) from the animals were collected randomly during 2009 to 2012. Sera were prepared from the collected blood samples, which were then examined for the presence of antibodies against Neospora using enzyme-linked immunosorbent assay (ELISA), Neospora modified direct agglutination test (N-MAT), and indirect fluorescent antibody test (IFAT). The seroprevalence rates of Neospora were found as 17.4% (n=245/1406) in cattle, 2.2% (n=8/358) in sheep, 40.8% (n=49/120) in horses, 52% (n=52/100) in donkeys, and 27% (n=73/270) in dogs. In this study, higher levels of Neospora infection were detected in cattle, horses, donkeys, and dogs. This is the first comprehensive study of Neospora infection in domestic animals in Iran. Further researches on molecular and bioassay studies and designing appropriate control strategies against neosporosis in Iran are necessary and strongly recommended. DOI: http://dx.doi.org/10.5455/javar.2014.a23 J. Adv. Vet. Anim. Res., 1(3): 119-124, September 2014